PLAYFULNESS, IRONY, AND HUMOR IN WILLY RUSSELL'S PLAY EDUCATING RITA - Ali Hadi Mulla Al Adilee (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Willy Russell is a British dramatist whose plays offer a new attitude towards life. Educating Rita as one of his most famous dramatic pieces accomplishes this goal through employing such comic features as irony, humor and playfulness. This article intends to analyze these elements in Educating Rita in order to reveal Russell's aim of writing this play. To do so, the writer has benefitted from the tents of Feminism because Russell employed Rita as a working class woman who has been deprived of an individual identity in order to reveal her attempts to free herself from the limitations that have been imposed on her due to her social standing and femininity. It will be concluded that Russell found irony, humor and playfulness as effective tools to achieve this purpose.